ANALISIS PERCEPATAN PADA PROYEK PEMBANGUNAN RUANG KELAS BARU MADRASAH IBTIDAIYAH NEGERI 5 MALUKU TENGAH DENGAN MENGGUNAKAN METODE CRASHING PROGRAM - Salong, Ahmat ikbal; Leuhery, Lenora; Abdin, Maslan (Jurusan Teknik Sipil, 2024)
There are several aspects of project implementation management, such as implementation plans, schedules, and others. The emergence of problems in the implementation management aspect hurts project implementation. Then the alternatives that are usually used to support the acceleration of activities is to increase working hours so that it has an impact on the total project cost. The Madrasah Ibtidaiyah Negeri 5 Maluku Tengah New Classroom Construction Project was chosen for the research study because it experienced delays. The CPM (critical path method) is used to analyze the project implementation time to obtain critical work that has no leeway days to be accelerated. The optimal time and cost are obtained from the Crash Program using the Crashing method by adding working hours to each accelerated critical work. From the acceleration, the cost slope value is obtained. the purpose of this research is to determine what work is critical in the project and also get the results of analyzing the calculation of time and cost of work after being accelerated. The result showed that the total normal project cost budget of Rp 2,891,000,000 with an implementation duration of 120 days, in conditions after crashing with an alternative of adding working hours for two hours obtained a cost of Rp 2,943,185,364 greater than the total project cost budget under normal conditions and a reduction in duration to 110 days or faster than the normal duration. The total cost slope value obtained was Rp 64,231,234.